2019
DOI: 10.1038/s41588-019-0360-8
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome segregation errors generate a diverse spectrum of simple and complex genomic rearrangements

Abstract: Cancer genomes are frequently characterized by numerical and structural chromosomal abnormalities. Here we integrated a centromere-specific inactivation approach with selection for a conditionally essential gene, a strategy termed ‘CEN-SELECT’, to systematically interrogate the structural landscape of missegregated chromosomes. We show that single-chromosome missegregation into a micronucleus can directly trigger a broad spectrum of genomic rearrangement types. Cytogenetic profiling revealed that missegregated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
182
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(204 citation statements)
references
References 78 publications
8
182
1
1
Order By: Relevance
“…It is possible that several micronuclei concurrently developed in a testicular germ cell and created both simple and catastrophic rearrangements. Consistent with this, Ly et al [2019] reported that chromosomal missegregation during mitosis can induce various genomic rearrangements including chromothripsis and amplifications. Alternatively, a hitherto unrecognized mechanism may have produced the transient genomic crisis in our case.…”
Section: Transient Multifocal Genomic Crisissupporting
confidence: 65%
“…It is possible that several micronuclei concurrently developed in a testicular germ cell and created both simple and catastrophic rearrangements. Consistent with this, Ly et al [2019] reported that chromosomal missegregation during mitosis can induce various genomic rearrangements including chromothripsis and amplifications. Alternatively, a hitherto unrecognized mechanism may have produced the transient genomic crisis in our case.…”
Section: Transient Multifocal Genomic Crisissupporting
confidence: 65%
“…In addition to the above described mutational events, we found that chromosome bridge formation predisposes to micronucleation, which could then initiate another round of chromothripsis downstream of bridge breakage (14, 17, 76). We attribute the high rate at which bridge chromosomes mis-segregate in the second mitosis to depletion of CENP-A nucleosomes, which provide the epigenetic specification of centromere identity (77, 78).…”
Section: Discussionmentioning
confidence: 80%
“…many individual circular DNA molecules (extrachromosomal DNA, ecDNA, alias double minute chromosomes, dmin) 1 . EcDNA can arise during genome reshuffling events like chromothripsis and are subsequently amplified 2,3 . This partially explains why such circular DNAs can consist of several coding and non-coding distant parts of one or more chromosomes 4 .…”
Section: Introductionmentioning
confidence: 99%